Peningkatan Kualitas Tidur Wanita Menopause Melalui Edukasi Kesehatan dan Latihan Pernafasan Dalam - Cholila, Nur; Umi Rohmatin (Health Care : Journal of Community Service, 2025)
Poor sleep quality is a common issue among menopausal women, potentially impacting their overall health and quality of life. This community service initiative aims to improve sleep quality for menopausal women in Kenanti Village, Tuban, through health education and deep breathing exercises. The topic selection stems from the high prevalence of sleep disturbances and the limited access to non-pharmacological solutions. The service method included counseling, demonstration and practice of exercises. The result shows a significant increase in the subjective sleep quality of the participants. It is concluded that deep breathing exercise education is effective in improving the sleep quality of menopausal women. Therefore, this program has the potential to be replicated in other regions and to be a special education for the community, especially menopausal women.